FAKTOR DETERMINAN TINGKAT KETAHANAN PANGAN RUMAHTANGGA PESERTA PROGRAM DESA MANDIRI PANGAN (DEMAPAN) DI PROVINSI RIAU - Henny Rasmiati; Djaimi Bakce; Shorea Khaswarina (DINAMIKA PERTANIAN, 2016)
Indonesian Government has impelemnt various programs to improve the community food security, one of them is Village Food Resiliance Program. The Prgram has been conducted by Indonesian Government since 2006. This study intend to analyze what determinant factors that influence participant household food security level after they join the village food resilience program in Riau Province. The multinomial logistic analysis results conclude that the determinant factors affecting food resilience of the participants of the Mandiri Pangan Village Program in Riau Province are the age of the household head, the number of household members and the size of the household landholdings